The Pesantren Leaders’ Visionary in Improving Khidmah Lil-Ummah Excellent Service - Izzul Maromi (Journal of Islamic Education Research, 2023)
Visionary in Khidmah Lil-Ummat Management is a method used in management in an educational institution. visionary is an effort or tips made by educational institutions in managing the service system with a good service system used to build the institution's Khidmah Lil-Ummat Management. KH. Ilyas Siraj and KH. Moh. Hefni Mahfudz, both are Islamic boarding school or pesantren leaders use one of these methods in the management of Khidmah Lil-Ummat. The purpose of this research is to understand and analyze how the visionary of pesantren leaders is in the Khidmah Lil-Ummat Management. This research uses a qualitative approach with a case study type of research. As a key instrument, researchers conduct research using additional instruments in the form of interview guides, observation guidelines and documents in the form of activity photos or software/hardware data about research activities. In the process, the researcher also checked the validity of the data by using data triangulation to obtain data validity. The research results obtained are the implementation of pesantren leaders visionary in Khidmah Lil-Ummat Management, carried out through five dimensions of pesantren leader visionary in Khidmah Lil-Ummat Management consisting of Showing Foresight, Creative Thinking and Motivating, Taking Risks, Coalition Building and Continuous Learning.